Multiorgan tuberculosis - Đokić Milomir; Bojić Ivanko; Mikić Dragan; Mladenović Ljubiša; Begović Vesna; Kuprešanin Srđan; Mirović Veljko; Dimitrijević Jovan (Vojnosanitetski Pregled)
Tuberculosis is an unusual infectious disease because of the latent period between the infection and the appearance of the disease may be prolonged for many weeks, months, or years as it is in case of the secondary tuberculosis. Tuberculosis in organs other than the lung has been observed for many years but has not always been recognized as tuberculosis, and it has been given many names. Extrapulmonary tuberculosis gained new importance, because it represented a progressively greater proportion of new cases. Multiple extrapulmonary sites were reported rarely except for one anatomical site, which was reported frequently. Extrapulmonary rates increase with age, so there are marked differences in age in specific rate patterns among the sites. Extrapulmonary tuberculosis occurred in respiratory organs other than lung, such as lymphatic, urogenital, and central nervous system, abdominal, osteoarticular, as well as tuberculosis of other organs such as skin, pericardium and endocrine glands. This case was reported to analyse clinical, morphologic and laboratory characteristics, method of diagnosis and the outcome in patients with multiorgan tuberculosis in order to explore the factors which might contribute to the decision making, concerning these forms of tuberculosis. Recent knowledge of pathogenesis was summarized as well as clinical presentation and the effects of cytokines produced by T lymphocytes and cellular population on antimycobacterial immune defences, and also susceptibility to tuberculosis. Mortality remains high and the treatment should start as soon as tuberculosis is suspected.